Mitochondrial chaperonin Hsp60: locations, functions and pathology - Cappello, Francesco; Macario, Alberto J. L. (Henry Stewart Talks, 2012)
Chaperonology, The chaperoning system, Chaperonopathies, Hsp60, Genetic Hsp60 chaperonopathies, Hsp60 in cancer, Update talk: Chaperonin system, Update talk: Maintenance of protein homeostasis, Update talk: Interaction with immune system, Update talk: Chaperone Hsp60, Update talk: Chaperonopathies, Update talk: Examples of Hsp60 aberrant PTM and their impact on function, Update talk: Doxorubicin, Update talk: Missense variants and pathogenicity
Updated at 2021/07/29